Emotional intelligence dimension on self-esteem of employees through the personality of leader - Johar, Siti Sarawati; Abdullah, Md. Akbal; Md. Yusoff, Rosman; Suhaimy, Khairul Azman; Isa, Khairunesa; Ismail, Fadillah (Science Publishing Corporation (SPC), 2018)
This paper concept focuses more on an analytical discussion of employee’s self-esteem from the perspective of emotional intelligence through the personality of leaders in the workplace. This is one of the challenges the application of psychology in the organization currently based on human capital. This discussion encompasses the conceptual of self-esteem, emotional intelligence, and personality, purpose of study, the influence, challenges and outlook. In fact, human capital development should be along the physical and material development of the country that we do not deny the growing momentum ahead of the years. All employees in any organization as a human entity that should be a high capacity of human capital in terms of emotional intelligence to produce the output and quality workmanship and value in the steady integrity. Then, the leader in the workplace should have a strong emotional intelligence to be able to translate into a treatment and a dynamic personality in influencing a more positive work climate. The end of this paper will demonstrate the need for all leaders have emotional intelligence that is based on the strength of the affective and personality ideal as a catalytic force to help enhance employee self-esteem. It also would allow employees to be able to form effective human resources.